2014
DOI: 10.1186/1477-7819-12-137
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of TMEM16A, PPFIA1, and FADD expression in invasive ductal carcinoma of the breast

Abstract: Background11q13 region is a frequently amplified locus in human malignancies. Among the genes located in this region, FADD is one of the alleged driving genes. Because amplification is not generally confined to a single gene and amplified genes may not show increased expression, we need to evaluate clinical significance of changes occurring in 11q13 region to understand their roles in carcinogenesis. Therefore, we screened expressions of FADD and closely located genes (PPFIA1 and TMEM16A) and evaluated the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Concomitant amplification of the 11q13 region in HNSCC [ 39 ] and over expression of FADD have, in combination, suggested this gene to be the driver of this amplicon [ 40 ]. As observed in this study, both these genes, in combination, are also identified to be predictive of prognosis in breast cancers [ 41 ]. Identification of these two genes from this cross-study/cross-platform analysis, necessitates detailed investigation as to their role in the disease and their clinical applicability as biomarkers and/or therapeutic targets.…”
Section: Discussionmentioning
confidence: 76%
“…Concomitant amplification of the 11q13 region in HNSCC [ 39 ] and over expression of FADD have, in combination, suggested this gene to be the driver of this amplicon [ 40 ]. As observed in this study, both these genes, in combination, are also identified to be predictive of prognosis in breast cancers [ 41 ]. Identification of these two genes from this cross-study/cross-platform analysis, necessitates detailed investigation as to their role in the disease and their clinical applicability as biomarkers and/or therapeutic targets.…”
Section: Discussionmentioning
confidence: 76%
“…Copy number data for this region are shown in Fig 2 . 11q13.3 amplification has been previously described in breast cancer,[ 26 , 27 ] specifically ILC, [ 28 – 30 ] and in oral squamous carcinoma where it was reported as prognostic of metastasis [ 31 ]. Within our dataset, amplifications were identified in CCND1 , FADD and ORAOV1 in all three punches from both foci.…”
Section: Resultsmentioning
confidence: 99%
“… 7 The upregulation of TMEM16A has also been shown in several cancers, such as breast and prostate cancer, 8 head and neck squamous cell carcinoma (HNSCC), 9 esophageal squamous cell cancer, 10 and human colorectal cancer. 11 It has been shown that TMEM16A activated the MAPK signaling proteins, and promoted the tumorigenesis and invasion of various cancers, such as HNSCC, 6 breast cancer, 12 , 13 and gastrointestinal stromal tumors. 14 However, the expression and role of TMEM16A in hepatocellular carcinoma have not been evaluated to date.…”
Section: Introductionmentioning
confidence: 99%